HUBUNGAN KREATIVITAS GURU DENGAN KEAKTIFAN BELAJAR SISWA KELAS TINGGI PADA MATA PELAJARAN BAHASA INDONESIA DI SDN 102 MARIO KABUPATEN BONE - Abd. Hafid; Mujahidah Mujahidah; Hikmah Suciati; Sudarto Sudarto (Bajang Institute, 2024)
This research is a correlational research which aims to determine whether there or there is not a correlation between the teacher creativity and the active learning of high grade students in Indonesian language subjects at SDN 102 Mario, Bone Regency. The population and sample in this study were all of the high grade students at SDN 102 Mario, in amount of 84 students. The data collection used a questionnaires and observation sheets. The data analysis techniques used a descriptive statistical analysis and an inferential statistical analysis. Based on the descriptive statistics results of the research, the average teacher creativity was of 55.83 (high category). Meanwhile, the average student learning activity was of 32.88 (medium category), rcount ≥ rtable (0.0971 ≥ 0.212) at a significance level of 5%. Thus, H is accepted and H0 is rejected. Conclusion: there is a correlation between the teacher creativity and the high grade students' learning activeness in Indonesian language subjects at SDN 102 Mario, Bone Regency with a very strong correlation level.